Thomas 'Jupiter' Harris : spinning dark intrigue at Covent Garden Theatre, 1767-1820 - Oakley, Warren (Manchester University Press, 2018)
This is a biography of Thomas Harris: confidant of George III, 'spin doctor', philanthropist, sexual suspect, brothel owner and the man who controlled Covent Garden Theatre for nearly five decades.